A Case Study at the University of West Florida on Improving Recruitment and Retention of Female Students in Engineering - Bhuvana Ramachandran; Chathapuram Ramanathan; Mohamed Khabou (ASEAN Journal of Science and Engineering Education, 2022)
Women have increased their numbers in many professions previously dominated by men, including law, business, medicine, and other STEM fields in the U.S; however, the number of women in engineering in the U.S. has not increased since the early 2000s. A survey conducted by the Society of Women Engineers reveals that as of Nov 2019, the percentage of women in the engineering workforce is 13% and the percentage of bachelor’s degrees awarded to women in engineering and computer science is 19.9%. The authors of this research article understand the need to recruit and retain more female students in engineering colleges that would result in an increased percentage of women in the engineering workforce. To achieve this goal, the authors hypothesize that exposing female students to engineering at an early age and educating their parents about the engineering profession will increase gender diversity in engineering fields. In this research paper, the authors have designed a survey that explores and builds on the underlying connections between female students’ aspirations, their parental motivation, the presence of engineers in their family/friends’ circle, and hands-on exposure to engineering. The results from the survey are used to develop capacity-building activities for local high school students at the university.